In silico Identification and Comparative Analysis of Hevea brasiliensis COBRA Gene Family - Putranto, Riza Arief; Martiansyah, Irfan; Saptari, Rizka Tamania (Proceeding International Conference on Science and Engineering, 2017)
In this paper, the H. brasiliensis COBRA gene family, alleged to be involved in laticifer differentiation, was identified from the public rubber tree genome of Reyan 7-33-97 clone. A comparative analysis was carried out against A. thaliana genomic database. This analysis has resulted to the in silico validation of thirteen putative genes encoding glycophosphatidylinositol anchors (GPI) proteins harbored by nine Hevea genomic scaffolds. The sequence’s similarity of HbCOBL against AtCOBL genes were ranged from the threshold 50 to 81.58% covering 151 to 458 amino acid residues, respectively. Three partial and ten full-length protein sequences of HbCOBL genes were annotated. The partial protein sequences ranged from 89 to 184 amino acid residues as opposed to the full-length proteins ranging from 160 to 471 amino acid residues. Two types of COBRA domains (pfam04833 and cl04787) were found among HbCOBL genes. Phylogenetic analysis has clustered two subfamilies. Nine HbCOBL genes (HbCOBL-B, HbCOBL-J, HbCOBL-C, HbCOBL-H, HbCOBL-F, HbCOBL-I, HbCOBL-M, HBCOBL-A, and HbCOBL-N) were clustered as COBRA gene subfamily-I. By contrast, four genes (HbCOBL-O, HbCOBL-P, HbCOBL-E, and HbCOBL-L) were clustered as COBRA gene subfamily-II. The HbCOB subfamily-II was marked by the addition of 203 residues in C-terminal which is different with Arabidopsis. The gene HbCOBL-C was the putative ortholog to AtCOB carrying the unique COBRA domain cl04787 with 74 amino acid residues. Taken together, these results showed that Hevea and Arabidopsis COBRA genes might share similar functions while differ in gene structure.